Dramatization of Children's Fantasy Messages in Dieng Hair in Digital Media - Marwan Mahmudi; Haekal Fajri Amrullah; Nono Sungkono (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
This study explains how digital media dramatizes fantasy messages about children with dreadlocks in Dieng. The purpose of this study is to explore the meaning of fantasy messages as a result of dramatization by digital media for children with dreadlocks in Dieng. This study departs from the fantasy theme concept that the content of the message is dramatized to trigger a fantasy chain, such as jokes, analogies, word games, stories, and so on Digital media. Data collection techniques with documentation looking for news in digital media. The results of the research from the Syntax category, the four media showed that Dieng dreadlocks were special children, with unique and fashionable looks. The Script category is said to be privileged not a curse, asking for a different suit than usual. The Thematic category is phrased with the ruwatan ceremony as 'returning a deposit. The Rhetoric category reveals the presence of officials and community leaders to strengthen the dramatization of cultural/traditional phenomena in the news frame. The conclusions and suggestions of the research that the influence of ideology, interests, and editorial policies imply that news is not as subjective as the general view.